Demografske značilnosti tuzelskih Slovencev in njihova organiziranost - Tomažič, Dušan (Dve domovini, 2025)
The article explores the history of the Slovenian settlement in the Tuzla Canton area of Bosnia and Herzegovina, dating back to the Austro-Hungarian period. It analyzes census data from 1910 to 2013, highlighting the impact of the Bosnian War on demographic changes. In 1993, due to humanitarian needs, the Slovene Community Association was established, bringing together 660 families and comprising nearly 1,700 members. Due to post-war emigration, only 51 individuals declared themselves as Slovenians in the 2013 census.
Keywords: Bosnia and Herzegovina; demografske spremembe; Društvo Slovencev; emigration; izseljevanje; Slovenci; Slovene Association; Slovenians; Tuzla Canton; Tuzlanski kanton